THE EFFECT OF THE WORK ENVIRONMENT AND WORK DISCIPLINE ON EMPLOYEE SPIRIT AT KOPKAR SAMPOERNA - Mayangsari, Firda; Adiwati, Mei Retno (Perpustakaan dan Penerbitan Unismuh Makassar, 2021)
Every company or agency must strive so that the factors included in the work environment will be cultivated in such a way that it has a good influence on employees to foster a high sense of work discipline. Work discipline is an important factor in regulating the behavior and ways of working of members in the organization. The rules are in the form of a set of values and norms that have been agreed upon by members of the organization to regulate how members of the organization behave in carrying out organizational activities. So every company or organization needs a competitive advantage to achieve its goals. The phenomenon that occurs at KopKar Sampoerna is basically the work environment at KopKar Sampoerna still needs some improvement, because it still doesn't pay attention to the physical environment in the workspace, such as the lack of availability of living rooms that are still combined into one room with the employee's workspace, setting the air temperature in the workspace is still not good even though it is equipped with cooling facilities, there is glass covered by a curtain so that the lighting in the workspace is lacking.